Diplomacy and Early Modern Culture
XII, 200 p.
Keywords: Offering a fresh approach to the study of the figure of the diplomat in the early modern period, this collection of diverse readings of archival texts, objects and contexts contributes a new analysis of the spaces, activities and practices of the Renaissance embassy.